Analisa Penjadwalan Dengan Metode CPM dan Line of Balance pada Pembangunan Proyek Perumahan Citraland Ambon - Renwarin, Philipus; Jamlaay, Octovianus; Hutubessy, Vector Reinhard Redolf (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The housing development project in CitraLand Ambon employs an average of S curve and bar chart scheduling methodologies. The scheduling initiative aims to ensure the completion of all ongoing housing developments according to the established timeline. The scheduling outcomes utilizing the S curve and Bar Chart for the construction of seven Jade-type residences indicate a work duration of 167 working days. In practice, experience indicates that delays frequently arise due to many circumstances. Consequently, a novel scheduling mechanism is implemented that must be tailored to the specific type of housing project. This study aims to plan the development of the Citraland Ambon housing project utilizing the Critical Path Method (CPM) for one Jade type house unit and the Line of Balance (LoB) for the building of seven Jade type houses, which will be compared to the current timeline. The Lo Bini technique often employs a uniform building type for the execution of housing project construction. Identifying the work group for standard and ongoing tasks is a key benefit of this strategy, which fundamentally prioritizes the volume of job types to avoid impeding subsequent tasks (successors and predecessors). The author's research of the CitraLand Ambon Housing project scheduling, utilizing the CPM approach, indicates that the construction length for one Jade type dwelling unit is 59 days. The application of the LoB approach on seven Jade-type dwellings requires 127 days. There is a discrepancy of 40 days when compared to the previous method's completion time of 167 days. Utilizing the Line of Balance method for planning is more productive and efficient.